Development and optimization of rapid resolution liquid chromatography (RRLC) method following solid-phase extraction for determination of anthocyanin in rat plasma - Sauji, Nadiratul Asyikin (2021)
The growing interest of anthocyanins in roselle has brought upon the importance of the compound’s analysis to investigate its pharmacological properties. Sensitive and specific analytical methods are required to accurately analyse the anthocyanin present in the sample. In this study, rapid resolution liquid chromatography (RRLC) was used to analyse cyanidin-3-O-glucoside chloride, one of the anthocyanins found in roselle. Spectrophotometric analysis and optimization of chromatographic conditions were performed to develop a suitable and precise RRLC method for the determination of the selected anthocyanin. Both liquid-liquid extraction (LLE) and solid-phase extraction (SPE) method were performed to evaluate the best extraction method of anthocyanin in the rat plasma sample. The optimised chromatographic method demonstrated that the mobile phase composition of 0.1% trifluoroacetic acid aqueous solution and acetonitrile in the ratio of 81:19, respectively with a flow rate of 0.5 mL/min, at 30°C column temperature and detection wavelength of 525 nm were suitable for RRLC analysis of cyanidin-3-O-glucoside chloride. SPE was chosen as the final extraction method in the study as it produced better peaks in the chromatogram compared to LLE. In conclusion, the developed RRLC method in this study can be used to determine anthocyanins in the future pharmacokinetic study of roselle.